Recent approach for preventing complications in upper gastrointestinal endoscopic submucosal dissection. Issue 1 (31st October 2021) - Hatta, Waku; Koike, Tomoyuki; Abe, Hiroko; Ogata, Yohei; Saito, Masahiro; Jin, Xiaoyi; Kanno, Takeshi; Uno, Kaname; Asano, Naoki; Imatani, Akira; Masamune, Atsushi
Abstract: Although endoscopic submucosal dissection (ESD) is a minimally invasive treatment method for upper gastrointestinal (GI) tumors, patients undergoing upper GI ESD sometimes fall into a serious condition from complications. Thus, it is important to fully understand how to prevent complications when performing upper GI ESD. One of the major complications in esophageal and gastric ESD is intraoperative perforation. To prevent this complication, blind dissection should be avoided. Traction‐assisted ESD is a useful technique for maintaining good endoscopic view. This method was proven to reduce the incidence of intraoperative perforation, which would become a standard technique in esophageal and gastric ESD. In gastric ESD, delayed bleeding is the most common complication. Recently, a novel prediction model (BEST‐J score) consisting of 10 factors with four risk categories for delayed bleeding in gastric ESD was established, and a free mobile application is now available. For reducing delayed bleeding in gastric ESD, vonoprazan ≥20 mg/day is the sole reliable method in the current status. Duodenal ESD is still challenging with a much higher frequency of complications, such as perforation and delayed bleeding, than ESD in other organs. However, with the development of improved devices and techniques, the frequency of complications in duodenal ESD has been decreasing. To prevent intraoperative perforation, some ESD techniques, such as using the distal tips of the Clutch Cutter, were developed. An endoscopic mucosal defect closure technique would be mandatory for preventing delayed complications. However, several unresolved issues, including standardization of duodenal ESD, remain and further studies are demanded.